Die kombinering van ekonomiese vooruitskattings in die Suid-Afrikaanse konteks - C. B. Calitz; E. V.D.M. Smit (South African Journal of Business Management, 1989)
In the literature on forecasting, consensus has been reached about improved forecasting accuracy brought about by the combination of two or more forecasts for a given variable. No consensus, however, exists about the exact way in which the various forecasts in the combination should be weighed. The evidence points towards simple weighing schemes. The present study utilizes South African macro-economic forecasts published by seven forecasters on eight variables to evaluate the benefits to be gained from combining forecasts and to evaluate the relative accuracy of a number of combination schemes. The results confirm the current views on the combination of forecasts in so far as combining forecasts have led to increased accuracy in forecasting. It further confirms the viewpoint that a simple or weighted arithmetic average of individual forecasts seems to be acceptable as instruments for combining forecasts.